Developing Asia's pension systems and old-age income support - Donghyun Park; Gemma B. Estrada (Asian Development Bank Institute (ADBI), 2012)
Old-age income support is becoming an issue of growing importance throughout Asia. This is especially true in East and Southeast Asia where the population is aging. This paper provides a broad overview of the current state of pension systems in the People's Republic of China, Indonesia, Republic of Korea, Malaysia, Philippines, Singapore, Thailand, and Viet Nam; analyzes the pension systems; and identifies their major structural weaknesses. The paper concludes with some specific policy directions for pension reform to strengthen the capacity of Asian pension systems in delivering economic security for the large and growing population of elderly looming on the region's horizon.
Keywords: H55; J11; J14; 330; asia; pension systems; old-age income support; population aging; pension reform; Alternde Bevölkerung; Altersvorsorge; Grundbedürfnisse; Rentenreform; Asien